PENGARUH MODAL AWAL, LAMA USAHA DAN JENIS DAGANGAN TERHADAP PENDAPATAN PEDAGANG DI PASAR TOS 3000 BATAM - Yuniasih, Kristina; Hikmah, Hikmah (SCIENTIA JOURNAL, 2021)
Market is a place where traders meet buyers, which will occur the sales and buying process. Income is influenced by several factors, namely initial capital, length of business and type of business. This research aims to determine the effect of initial capital, length of business and type of trade on trading income in the Tos 3000 Batam market, either simultaneous or partially. The population and sample in this research is traders in the Tos 3000 Batam market. The technique or data collection is using a questionnaire, the method of analysis in this research is uses multiple linear regression analysis hypothesis using the T and F test by SPSS application version 25. The results of this research indicate that simultaneous and partially initial capital, length of business and type of trade have a positive and significant effect on the income of traders in Tos 3000 Batam market.